The variability of Titan's magnetic environment - Bertucci, Cesar (2009)
With a mean orbital radius of 20.2 Saturnian radii (1 Saturn radius RS=60,330 km), Titan is usually located within the kronian magnetosphere. 3.5 years of Cassini magnetometer observations in the vicinity of Titan´s orbit reveal that the moon´s magnetic environment is strongly affected by the presence of Saturn´s magnetodisk. As a result of the disk´s solar-wind-induced asymmetry, Titan is exposed to quasi-dipolar fields in the noon sector, and planetward, swept-back fields in the dawn, dusk and midnight sectors. These magnetic properties indicate that the moon is, on average, south of the central current sheet and immersed in Saturn´s rotating magnetospheric plasma for all local times (SLT). At a given SLT, Titan´s distance from the central current sheet associated with the magnetodisk depends on the solar wind pressure and on the phase of the Saturn´s kilometric radiation (SKR). The influence of the solar wind is present at all SLT (although dominant in the noon sector), whereas the SKR modulation seems to affect the magnetic field to first-order at least in the dawn sector. Near dawn local times, Titan tends to be farther from the disk at SKR longitudes around ˜140° and closer to it for longitudes around ˜320°. Depending on these factors, Titan is exposed to either: (i) a ‘magnetodisk lobe’ regime where the plasma beta is low and fields are radially ‘stretched’ and usually stronger or (ii) a ‘current sheet’ regime—characterized by quasi-dipolar, relatively weak fields and a high-beta plasma.